Development of augmented reality flashcards on cultural diversity to improve elementary students’ learning outcomes - Amelia Ellena Candra; Tri Astuti (Jurnal Prima Edukasia, 2026)
This research aims to develop, determine the feasibility, and test the effectiveness of Augmented Reality-based Flashcards on the topic of cultural diversity in improving elementary school students' learning outcomes. The research method used is Research and Development (R&D) using the Borg & Gall development model. The subjects of this research were fourth-grade students at SDN Bringin 02 Semarang. Data collection techniques included interviews, observations, questionnaires, tests, and documentation, which were conducted in November 2025. The research instruments consisted of interviews, documentation, needs and response questionnaires, pretest and posttest questions, and expert validation sheets. The pretest and posttest trial questions were analyzed using validity, reliability, item difficulty index, and item discrimination index calculations. Data analysis was performed using normality tests, T-tests, and N-gain tests. The results of this research are the creation of a feasible and effective augmented reality-based flashcard medium to improve fourth-grade students' learning outcomes in Natural and Social Sciences, specifically on the topic of Indonesian cultural diversity at SDN Bringin 02. Therefore, this medium can be recommended as an innovative learning alternative for elementary schools to support interactive and meaningful Natural and Social Sciences learning.